(untitled) (Huellas, 2021)
Among the biophysical indicators that link the availability of resources in a territory with the consumption of these resourses by a population are the Ecological Footprint and the Local Load Capacity, which together suggest the degree of sustainability of a territory. The aim of the study is to analyze the sustainability situation of the General Pueyrredon partido and the main city (Mar del Plata) from an analisys of two indicators: Ecological Footprint (HE) and Local Load Capacity (CCL). The methodology taking into account the guidelines proposed by Wackernagel and Rees (1996), was adjusted to the characteristics of the area, then the CCL was estimated. Finally, the relationships between both indicators were analyzed. The results shown that the demand of resourses exceeds the CCL of the General Pueyrredon partido because the HE is greater than the CCL. Therefore, a part of the local demand is imported (CCA) from other ecosystems (import of biocapacity).